Translation, Validity, and Reliability of Mental Health Literacy and Help-Seeking Behavior Questionnaires in Indonesia - Kaligis, Fransiska; Ismail, R. Irawati; Wiguna, Tjhin; Prasetyo, Sabarinah; Indriatmi, Wresti; Gunardi, Hartono; Pandia, Veranita; Minayati, Kusuma; Magdalena, Clarissa Cita; Nurraga, Garda Widhi; Anggia, Muhammad Fariz; Pamungkas, Subhan Rio; et al. (Frontiers in Psychiatry, 2022)
Background and Aim: Mental health is an integral part of adolescent wellbeing. However, only few adolescents understand the importance of mental health and are aware of the right time to seek help. Lack of knowledge and stigma may impede help-seeking behavior. To assess these aspects, three questionnaires have been developed in the English language. This study aims to assess the validity and reliability of an Indonesian version of the Mental Health Literacy and Help-Seeking Behavior set of questionnaires among adolescents in Indonesia. Methods: This is a cross-sectional study that used The Mental Health Literacy and Help-Seeking Behavior set of questionnaires developed by Kutcher and Wei. The set consists of three questionnaires: the Mental Health Knowledge, Attitude Toward Mental Health, and Help-Seeking Behavior questionnaire. The study was conducted between October 2020 and January 2021 with 68 first-year medical students at the University of Indonesia, who represented adolescents in a transitional phase. The questionnaires were translated into the Indonesian language by a bilingual psychiatrist and reviewed by 10 expert psychiatrists to determine content validity [Item-Level Content Validity Index (I-CVI) and Scale-Level Content Validity Index (S-CVI)]. Cronbach's alpha values were used to assess internal consistency (reliability). Results: The content validity test produced positive results with an I-CVI scores of 0.7–1.0 and S-CVI scores of 0.87, 0.90, and 0.99 for the knowledge, attitude, and help-seeking behavior questionnaires, respectively. For the reliability test, Cronbach's alpha values were 0.780 for the attitude questionnaire and 0.852 for the help-seeking behavior questionnaire, while the value for the knowledge questionnaire was 0.521. Conclusion: The ability to properly measure mental health through the availability of accessible, valid, and understandable tools plays an important role in addressing mental health issues among adolescents. In the current study, the Indonesian translations of all three questionnaires examining knowledge, attitude, and help-seeking behavior were considered to be valid and reliable.